2000
DOI: 10.1146/annurev.physchem.51.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Imaging Measurements of Ultrathin Organic Films

Abstract: The surface-sensitive optical technique of surface plasmon resonance (SPR) imaging is used to characterize ultrathin organic and biopolymer films at metal interfaces in a spatially resolved manner. Because of its high surface sensitivity and its ability to measure in real time the interaction of unlabeled biological molecules with arrays of surface-bound species, SPR imaging has the potential to become a powerful tool in biomolecular investigations. Recently, SPR imaging has been successfully implemented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
342
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(357 citation statements)
references
References 85 publications
4
342
0
3
Order By: Relevance
“…Angular dependent intensities of SPCECL (bottom). The upper panel shows the reflectivity of the gold film calculated using a gold dielectric constant of ε m = −10.5 + 1.49i and the software from [23,24] and http://corninfo.chem.wisc.edu Emission spectra of [Ru(bpy) 3 ] 2+ (top) and of SPCECL in acetonitrile (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…Angular dependent intensities of SPCECL (bottom). The upper panel shows the reflectivity of the gold film calculated using a gold dielectric constant of ε m = −10.5 + 1.49i and the software from [23,24] and http://corninfo.chem.wisc.edu Emission spectra of [Ru(bpy) 3 ] 2+ (top) and of SPCECL in acetonitrile (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…This method is label free, in situ, surface sensitive, measures in realtime and, by measuring the light source with a microscope or camera, spatially resolved measurements can be made using a method termed surface plasmon resonance imaging [76][77][78]. This approach has been applied to the study of protein-material interactions on a microarray format [79].…”
Section: Assessment Of Biological Response To Microarraysmentioning
confidence: 99%
“…This sensor detects changes in the refractive index induced by molecules near the surface of noble metal thin films. 99,100 Riboh et al 101 demonstrated LSPR nanobiosensor study on the prototypical immunoassay involving biotin (B) and anti-biotin (AB). The optical biosensors detect change in local refractive index by monitoring the LSPR extinction maximum with UV-Visible spectroscopy.…”
Section: Immunoassay (Detection Of Ab-ag Reaction)mentioning
confidence: 99%